2019
DOI: 10.3390/ma12091571
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Alkali-Activated Slag Paste Using New Colloidal Nano-Silica Mixing Method

Abstract: Previous studies of alkali-activated slag cement (AASC) using nano-silica have mentioned mostly powdered nano-silica and binder weight replacement methods, which have a rapid decrease in fluidity, a short setting time and a low nano-silica replacement rate (< 5%). In this study, colloidal nano-silica (CNS) was used and the mixing-water weight substitution method was applied. The substitution method was newly applied to improve the dispersibility of nano-silica and to increase the substitution rate. In the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
(140 reference statements)
1
5
0
Order By: Relevance
“…Simultaneously, the use of NS tends to increase the proportion of smaller pores, by disconnecting continuous pores from discontinuous ones and subdividing larger pores into smaller ones; thus producing a material with a finer pore structure, which exhibits lower transport properties. The MIP measurements in the present study, as well as those of other authors [36,46,47,48], confirm that total porosity decreases significantly in the presence of NS in the cement matrix, when the optimal amount of NS is incorporated. Therefore, as reported in this study, NS-modified composites exhibit denser microstructures with lower water absorption, which might potentially prevent the ingress of aggressive solutions to the pore structure [12,14,49,50,51].…”
Section: Discussionsupporting
confidence: 91%
“…Simultaneously, the use of NS tends to increase the proportion of smaller pores, by disconnecting continuous pores from discontinuous ones and subdividing larger pores into smaller ones; thus producing a material with a finer pore structure, which exhibits lower transport properties. The MIP measurements in the present study, as well as those of other authors [36,46,47,48], confirm that total porosity decreases significantly in the presence of NS in the cement matrix, when the optimal amount of NS is incorporated. Therefore, as reported in this study, NS-modified composites exhibit denser microstructures with lower water absorption, which might potentially prevent the ingress of aggressive solutions to the pore structure [12,14,49,50,51].…”
Section: Discussionsupporting
confidence: 91%
“…The compressive strength values of alkaline activated slag cement using the same mixed activation of 5% NaOH + 5% Na 2 SiO 3 and 10% NaOH + 10% Na 2 SiO 3 were measured higher than MS [28]. Both 5% and 10% activators showed higher strength values than MS, and 10% activator showed better compressive strength value than 5%.…”
Section: Compressive Strengthmentioning
confidence: 84%
“…The cause of this result was reported that excessive gypsum caused expansion inside the specimen, increasing porosity and decreasing compressive strength. A study by Kim et al [28] using 5% NaOH + 5% Na 2 SiO 3 and 10% NaOH + 10% Na 2 SiO 3 showed a sharp decrease in the total porosity of the 10% activator than 5%. Increasing the concentration of the activator promotes the formation of the hydration reactant and creates a dense structure, reducing the porosity.…”
Section: Hydration Productsmentioning
confidence: 91%
See 2 more Smart Citations